2019
DOI: 10.1007/s11998-019-00292-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobization, smoothing, and barrier improvements of cellulose nanofibril films by sol–gel coatings

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Other recent studies [63] show that the barrier properties of NFC films are improved by hydrophobization of fibrils surface using sol-gel methods. By sol-gel methods, coatings are relatively dense and homogeneous coating layers are obtained with strong adhesion leading to decrease of surface hydrophilicity and water vapor transmission rate.…”
mentioning
confidence: 94%
“…Other recent studies [63] show that the barrier properties of NFC films are improved by hydrophobization of fibrils surface using sol-gel methods. By sol-gel methods, coatings are relatively dense and homogeneous coating layers are obtained with strong adhesion leading to decrease of surface hydrophilicity and water vapor transmission rate.…”
mentioning
confidence: 94%
“…It should be emphasized that nanotopographic features (according to SEM) on both papers were similar, while the initial microtopography was different, which could partially influence the wettability. Wettability changes were also observed for Si–O–Si, Al–O, and Zr–O ceramic-based sol-gel treated CNF films by Vartiainen et al, who reported an increase in water contact angle from 54 to 102 degrees after the coating [ 34 ]. In this study, decreased water vapor transmission was also reported.…”
Section: Resultsmentioning
confidence: 82%
“…To bypass this issue, a smoothening layer can be inserted between the cellulose films and the given functional layer, typically the electrode. This approach (1) can protect the substrate from entering in contact with liquids that swell or dissolve cellulose; (2) can act as a smoothening layer to reduce the overall surface roughness of the substrate; (3) it can increase the substrate gas barrier properties (Vartiainen et al, 2020) (Table 1).…”
Section: Substratesmentioning
confidence: 99%